A Discourse on AI and Society: Your calculus may be greater than his calculus But will it pass the Sullenberger Hudson River test?. Issue 2 (2020) - O'Neill, Brenda; Stapleton, Larry; Gill, Karamjit S.; Brandt, Dietrich
Abstract: This paper has been submitted as Survey Paper on technology development with the emphasis on manufacturing in view of their impact on humans, society, the environment and international stability. It deals with automation per se, the "Factory of the Past" and the "Factory of the Future" and "Industry 4.0", also referring explicitly to AI systems. It thus incorporates Looking back as well as Looking forward . Considering the complexity and the wide span of such a theme, we are expecting a discourse with a wide spectrum of participants. In the center of our paper stands the engineer, philosopher and author Michael Cooley from Ireland, and his recent poem Insulting Machines. It means that we are using the narrative patterns of poetry leading up to Cooley's fight for the - still controversial - concept of Human Centered Technology Design .